(untitled) (Research, Society and Development, 2021)
Equiangular Channel Pressing (ECAP) is by far the most promising technique, by the severe plastic deformation (SPD) method, being able to produce large volumes of materials sufficient for practical applications. The ECAP process can be repeated until refining saturation is reached, leading to large amounts of shear strain. The reason behind the exceptional properties obtained in materials processed by ECAP was attributed to the microstructure of the material obtained in this deformation process. This work investigated the ECAP strain variables in the literature in order to analyze the effect of each of these on the microstructure of processed materials. The articles were collected from the following databases: ScienceDirect and the Scientific Electronic Library Online (SciELO) electronic library, as they include national and international literature. Based on the results found, it could be seen that several parameters must be analyzed to deform pure metals and alloys, to refine the microstructure, such as bending angle and channel angle of the strain matrix, number of passes, and pressing temperature. It was possible to verify that changes in these variables configure changes in the microstructure.